Globalisation: New Opportunities and Challenges to Business and the Population - Povilaitis, Bronius (Ekonomika, 2002)
Globalisation is the penetration of the global market into the life of the countries, caused by the strengthening international financial markets, rising world trade, creation of multinational businesses and progress in telecommunications. The present analysis of globalisation and the new opportunities and challenges it presents to businesses and the population attempts to take a broader view of the issue. We have tried to take a look at both sides of the globalisation process and assess not only the huge changes it brings to the world but also to review the contradictory impact it makes on man and the world inhabited by him. The benefits of globalisation are obvious: it is faster growth, higher standards of life and new opportunities. Yet far from all countries and all people are able to use the advantages offered by globalisation. Globalisation does not give heed to borders; it progresses every day and involves an increasing number of people. President Thabo Mbeki of South Africa, speaking at the World Summit for Sustainable Development held from August 26 to September 4, 2002, in Johannesburg, called the wealthy countries “islands of welfare”, surrounded by an “ocean of poverty”, and urged to stop the “global apartheid” of the poor countries. “Poverty, underdevelopment, inequality among countries and within countries together with the aggravating global ecological crisis throw a dark shadow on the whole world,” said President Mbeki. In analysing the new environment and the changes that are brought about by the unstoppable phenomena of globalisation spread more or less throughout the whole world, we have only two possibilities: we may rejoice at the new breathtaking prospects of new discoveries, or cringe in fear of drowning. The experience of most developed countries clearly indicates that the speed of social and economic development in any country is directly dependent on the education of its people, on the focused and constructive, creative energy in developing business and accumulating financial expertise. This is why education should doubtlessly be the priority in Lithuania. While the results of the ongoing changes may become evident only in several months or even several years, we should be always prepared to new challenges. The time has come to make use of what we have already accumulated, assess our strengths and weaknesses and model our actions, our place and ability of our business and people to compete in the European Union and other markets of the increasingly globalised world.